การพัฒนาครูไทยเพื่อการปฏิรูปการศึกษา - บุศรากูล, ธีระพงศ์ (วารสาร ศึกษาศาสตร์ มมร; Vol 7 No 2 (2019): วารสารศึกษาศาสตร์ มมร ปีที่ 7 ฉบับที่ 2 (กรกฎาคม - ธันวาคม 2562), 2020)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาสภาพปัญหาปัจจุบันของครูไทย  ศึกษาคุณลักษณะของครูไทยที่มีคุณภาพ  และศึกษาการพัฒนาครูไทยเพื่อการปฏิรูปการศึกษา  ทำการเก็บข้อมูลโดยใช้แบบสอบถาม  สอบถามกับครูในโรงเรียนประถมศึกษา  โรงเรียนมัธยมศึกษา  โรงเรียนสงเคราะห์  และโรงเรียนพิเศษทั่วประเทศไทยที่สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน  กระทรวงศึกษาธิการ  จำนวน  384 คน  โดยการหาขนาดกลุ่มตัวอย่างจากตารางของ  Krejcie & Morgan และการสังเคราะห์เอกสาร นำข้อมูลมาวิเคราะห์โดยใช้สถิติเชิงพรรณนา  ได้แก่  ความถี่และค่าร้อยละ ผลการวิจัย  พบว่า  ครูส่วนใหญ่เป็นเพศหญิงและอยู่ในภูมิภาคภาคใต้  จุดอ่อนของตัวครูไทยที่ประสบในปัจจุบันคือ ครูขาดประสบการณ์และความสามารถในการถ่ายทอดความรู้ให้กับนักเรียน  ปัญหาการศึกษาที่ครูประสบส่วนใหญ่ คือ ขาดแคลนบุคลากร และครูที่จบตรงตามสาขา  การแก้ปัญหาการศึกษาในท้องถิ่นที่ควรแก้ปัญหา คือ กรณีที่ครูได้รับมอบหมายให้สอนในสาขาที่ตนเองไม่ได้จบมา  ครูต้องหมั่นศึกษาหาความรู้เพิ่มเติมและพัฒนาตนเองให้มีความพร้อมอยู่เสมอและครูเห็นว่าควรมีการปฏิรูปการศึกษา เพราะการศึกษาจะได้มีความก้าวหน้าและพัฒนาสู่สากลและทันต่อเทคโนโลยี  ส่วนลักษณะของครูไทยที่มีคุณภาพ มีดังต่อไปนี้ 1) มีจิตวิญญาณของความเป็นครู  2) มีความรู้ ความสามารถทักษะการจัดการเรียนรู้และการวัดประเมินผล  3) มีทักษะความสัมพันธ์ระหว่างบุคคลและความรับผิดชอบ  4)   อำนวยความสะดวกในการเรียนรู้ที่มีประสิทธิภาพ  และ 5) แสวงหาความรู้ในการพัฒนาตน พัฒนาผู้เรียนและพัฒนาการเรียนการสอนอย่างสม่ำเสมอ  และในการพัฒนาครูไทย  หน่วยงานภาครัฐหรือหน่วยงานที่เกี่ยวข้องในการพัฒนาครูไทยจะต้องดำเนินการจัดการพัฒนา ดังต่อไปนี้  1) ส่งเสริมให้ครูพัฒนาตนเองอย่างต่อเนื่อง เช่น การเข้าประชุม สัมมนา ศึกษาต่อ ดูงาน รับการนิเทศ  เรียนรู้และปฏิบัติการสอนจนเกิดเป็นความชำนาญ   2)   สร้างเครือข่ายในการพัฒนาครูทั้งในระดับสถานศึกษาและนอกสถานศึกษาเพื่อให้เกิดการแลกเปลี่ยนเรียนรู้ระหว่างครูด้วยกัน เช่น เครือข่ายเสมือนจริง (ออนไลน์) เครือข่ายครูเฉพาะสาขาวิชา เครือข่ายครูสอนดี และเครือข่ายครูทั่วไป               3) พัฒนาครูโดยกระบวนการมีส่วนร่วมขององค์กรในระดับพื้นที่ทั้งภาครัฐ เอกชนและท้องถิ่น  และ 4)  จัดให้มีคูปองการพัฒนาครูประจำปีเพื่อจัดสรรให้ครูแต่ละคนได้รับการพัฒนาโดยพิจารณาจากผลสัมฤทธิ์ทางการเรียนของผู้เรียนเพื่อปรับปรุงการจัดเรียนการสอนและนำผลจากการพัฒนาตนเองไปใช้เป็นส่วนหนึ่งของการประเมินผลงานครู ABSTRACT This research aimed to examine Thai teachers' present state of problems; to study characteristics of quality Thai teachers; and to investigate Thai teacher development for educational reform. The data were collected through questionnaires, which were distributed across Thailand to 384 teachers in primary, secondary, welfare and special education schools under the auspices of the Office of Basic Education Commission, Ministry of Education. Krejcie & Morgan's table was used in sample size determination. The document synthesis was conducted, while the acquired data were analyzed using the descriptive statistics, namely, frequency and percentage.                 According to research results, most teachers were female and lived in the southern region of Thailand. Currently, it was found that the weakness of teachers involved their inexperience and inability to disseminate knowledge to students. Besides, the educational problem suffered by teachers was the lack of personnel and of teachers with discipline-specific qualifications. Respecting the possible solution for educational problem in local area, teachers should always broaden their knowledge and engage in self-development in order to be prepared for teaching subjects, which were not their graduated major program. They also viewed that the educational reform should be made for the sake of educational advancement, development towards universality and response to technologies. Additionally, the characteristics of quality teachers included 1) teacher's spirit, 2) knowledge and skills of learning management and assessment, 3) interpersonal relationships skills and responsibilities, 4) ability to efficiently facilitate learning, and 5) frequent acquisition of knowledge for self-, learner and instructional developments. With regard to Thai teacher development, public agencies or organizations involving in such issue should take the following development initiatives: 1) encouragement for continual teacher development e.g. conference attendance, further education, field study, receipt of supervision and acquisition of expertise through relevant learning and teaching practicum, 2) creation of teacher development networks in- and outside educational institutions for knowledge exchange among teachers such as virtual (online) networks, discipline-specific teacher networks, networks of teachers with good teaching techniques and general teacher networks, 3) teacher development with the participation of public, private and local organizations, and 4) introduction of annual teacher development coupons, which were distributed on the basis of learners’ accomplishments to individual teachers for the instructional improvement purpose. Lastly, self-development outcomes were also incorporated as a part of teacher evaluation.